Antibiotic‐Releasing Silk Biomaterials for Infection Prevention and Treatment. (26th September 2012) - Pritchard, Eleanor M.; Valentin, Thomas; Panilaitis, Bruce; Omenetto, Fiorenzo; Kaplan, David L.
Abstract Effective treatment of infections in avascular and necrotic tissues can be challenging due to limited penetration into the target tissue and systemic toxicities. Controlled‐release polymer implants have the potential to achieve the high local concentrations needed while also minimizing systemic exposure. Silk biomaterials possess unique characteristics for antibiotic delivery, including biocompatibility, tunable biodegradation, stabilizing effects, water‐based processing, and diverse material formats. The functional release of antibiotics spanning a range of chemical properties from different material formats of silk (films, microspheres, hydrogels, coatings) is reported. The release of penicillin and ampicillin from bulk‐loaded silk films, drug‐loaded silk microspheres suspended in silk hydrogels and bulk‐loaded silk hydrogels is investigated and the in vivo efficacy of the ampicillin‐releasing silk hydrogels is demonstrated in a murine infected‐wound model. Silk sponges with nanofilm coatings are loaded with gentamicin and cefazolin, and release is sustained for 5 and 3 days, respectively. The capability of silk antibiotic carriers to sequester, stabilize, and then release bioactive antibiotics represents a major advantage over implants and pumps based on liquid drug reservoirs, where instability at room or body temperature is limiting. The present studies demonstrate that silk biomaterials represent a novel, customizable antibiotic platform for focal delivery of antibiotics using a range of material formats (injectable to implantable).